The Nature of Assertoric-Force and the Truth in Logic: An Elucidation of Fregean Truth in the Light of Husserl’s Theory of Doxic-Modification - Song, Gao (Organon F, 2011)
The unique relation between logic and truth (protorelation) is crucial for understanding Fregean conception of logic. Frege has an insight that the nature of logic resides in the “truth“, which he finally locates in the assertoric-force of a sentence. Though Frege admits that assertoric-force is ineffable in ordinary language, he coins in his conceptual notation for such a force a much-disputed sign, i.e., judgment-stroke. In this paper, I will try to demonstrate that judgment-stroke is not adequate for the task its inventor has assigned to it. Accordingly, it is misconceived and inconducive to clarify Frege’s vague insight into the protorelation. The mistake of judgment-stroke for the sign of assertoric-force has its root in Frege’s ignorance of the significant difference between “judgment” and assertion”, which will be elucidated at length in the light of Husserl’s theory of “doxic-modification“. In the end, based on a further elucidation of the activity of assertion, I will advance a tentative interpretation of the vague insight Frege has concerning the protorelation.